Application of a two-fluid two-point model to SolEdge2D-EIRENE simulations of TCV H-mode plasma. (January 2019) - Nespoli, F.; Bufferand, H.; Valentinuzzi, M.; Fedorczak, N.; Ciraolo, G.; Serre, E.; Marandet, Y.; Maurizio, R.; De Oliveira, H.; Labit, B.; Komm, M.; Faitsch, M.; et al.
Highlights: Simulations of a TCV H-mode plasma have been performed with SolEdge2D-EIRENE, featuring carbon impurities sputtered from the wall. The agreement with the experimental data is in general satisfactory, but the application of the two-point model to the simulation results leads to apparent momentum gain. The application of a two-fluid two-point model to the simulation results overcomes this apparent discrepancy. Abstract: The edge and scrape-off layer (SOL) plasma of the inter-ELM phase of an H-mode discharge from the TCV tokamak is modeled with the transport code SolEdge2D-EIRENE (Bufferand et al. Nuclear Fusion 55 (2015)). The numerical simulations, in presence and in absence of C impurities sputtered from the first wall, are presented and compared with the experiments, finding an overall good agreement. The application of the standard two-point model to the simulation results leads to an apparent momentum gain along the divertor leg. A two-fluid two-point model featuring thermally decoupled ions and electrons is introduced and applied to the simulation results, overcoming this apparent discrepancy.